2021
DOI: 10.1080/20004508.2021.1883910
|View full text |Cite
|
Sign up to set email alerts
|

Teacher characteristics as predictors of mathematics attitude and perceptions of engaged teaching among 12th grade advanced mathematics students in the U.S

Abstract: The present study examined the 2015 Trends in International Mathematics and Science Study "Advanced" data to examine how the educational credentials of maths teachers and other teacher characteristics were related to attitude towards advanced mathematics and perceptions of engaged teaching among 12th-grade students enrolled in advanced mathematics courses in the U.S. As attitudinal outcomes in this study, two measures of attitude towards mathematics were employed-the Students Like Learning Advanced Mathematics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…In the 2021 study carried out by the authors of this study (Smith et al, 2021), some notable gender differences in the effect of school belonging on attitudes toward advanced mathematics were noted. In Portugal, it was observed that the relationship between students' sense of school belonging and both Students Value Advanced Mathematics and Students Like Learning Advanced Mathematics was significantly stronger for males than females.…”
Section: Attitudes Toward Sciencementioning
confidence: 76%
See 3 more Smart Citations
“…In the 2021 study carried out by the authors of this study (Smith et al, 2021), some notable gender differences in the effect of school belonging on attitudes toward advanced mathematics were noted. In Portugal, it was observed that the relationship between students' sense of school belonging and both Students Value Advanced Mathematics and Students Like Learning Advanced Mathematics was significantly stronger for males than females.…”
Section: Attitudes Toward Sciencementioning
confidence: 76%
“…When comparing the results of this study predicting attitudes toward advanced physics to the findings of Smith et al (2021), who used the TIMSS 2015 Advance data to how students' sense of school belonging predicted attitudes toward advanced mathematics, some notable observations emerged. First, for both math and physics attitudinal outcomes, students' sense of school belonging was as an important predictor-statistically significant in each country, and emerging as either the most important or second-most important among the four predictors considered (sense of school belonging, parental education, gender, and physics/math achievement).…”
Section: Comparisons With Attitude Toward Mathematicsmentioning
confidence: 83%
See 2 more Smart Citations
“…Dalam penelitian ini pengumpulan data menggunakan skala likert dan data yang dikumpul melakukan diuji validitas dan uji reliabilitas menggunakan aplikasi SPSS statistik 24. Pernyataan kuesioner berasal dari instrumen Alves et al, (2016); Smith et al, (2022) dan dimodifikasi sesuai dengan keperluan penelitian.…”
Section: Pendahuluanunclassified